2014
DOI: 10.1002/app.41381
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical, morphological, and thermal properties of nanotalc reinforced PA6/SEBS‐g‐MA composites

Abstract: Ternary butylene‐styrene‐g‐maleic anhydride (SEBS‐g‐MA) (100/20 w/w) blend with varying content of nanotalc (1, 3, and 5 wt %) were prepared by melt compounding followed by injection molding. Thermal properties were investigated by thermogravimetric analysis (TGA) and the results show that the thermal properties of nanocomposites are slightly improved by the addition of nanotalc content. The morphology of nanocomposites using wide angle X‐ray diffraction (WAXD) and transmission electron microscopy (TEM) reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 91 publications
0
9
0
Order By: Relevance
“…Hemlata et al [81] PA6/SEBS-g-MA/nanotalc method and parameters are also important for getting balanced properties in hybrid nanocomposites. He et al [73] studied PA6/SEBS-g-MA/organoclay (DK) hybrid nanocomposites with GMA as compatibilizer (80/ 20/4/1 wt/wt/phr/phr) and compared with, pure PA6, PA6/DK (80/4), PA6/SEBS (80/20), and PA6/GMA (80/1) which were melt-processed under same conditions.…”
Section: A and Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemlata et al [81] PA6/SEBS-g-MA/nanotalc method and parameters are also important for getting balanced properties in hybrid nanocomposites. He et al [73] studied PA6/SEBS-g-MA/organoclay (DK) hybrid nanocomposites with GMA as compatibilizer (80/ 20/4/1 wt/wt/phr/phr) and compared with, pure PA6, PA6/DK (80/4), PA6/SEBS (80/20), and PA6/GMA (80/1) which were melt-processed under same conditions.…”
Section: A and Bmentioning
confidence: 99%
“…Hemlata et al [81] studied the properties of PA6/SEBSg-MA/nanotalc (100/20/1-5 wt/phr/wt) composite with increasing nanotalc content. Morphology of the composite was studied using TEM analysis, and it was found that the nanotalc was dispersed in both PA6 as well as SEBSg-MA phase as it was coated with silanol groups.…”
Section: A and Bmentioning
confidence: 99%
“…The value of B depends on the size and loading of filler as well as on the thickness and extent of interphase. 32,35 The correlation graph of experimental tensile value with that of theoretical value obtained using the Pukanszky model is shown in Figure 8. As clear from the figure, the Pukanszky model exhibits a better fit in the case of PBMA/Nd 2 O 3 nanocomposites.…”
Section: Resultsmentioning
confidence: 97%
“…Many theoretical equations are used to predict the effect of various factors (size, shape, aspect ratio, filler concentration, the extent of interfacial interaction between filler and polymer matrix) toward the improved tensile properties of polymer nanocomposites. 4,32 In the present work theoretical models suggested by Einstein, Mooney and Pukanszky equations are employed to predict the tensile properties of PBMA/Nd 2 O 3 nanocomposites. The experimental value obtained from the tensile analysis is compared with the theoretical tensile strength to predict the reinforcing factors behind the enhanced mechanical properties of polymers.…”
Section: Resultsmentioning
confidence: 99%
“…For example, talc with a particle size of 44 µm is used in ceramics and paints, 8-12 µm in paper, 7 µm in cosmetics, and 2 µm or smaller in rubber [2]. In addition, the nanoscale talc recently received attention for its application in areas such as improving the heat resistance of nanocomposites, and for use in waste water filter materials [3][4][5].…”
Section: Introductionmentioning
confidence: 99%